Humoral and Cellular Response of Frontline Health Care Workers Infected by SARS-CoV-2 in Nice, France: A Prospective Single-Center Cohort Study - Cremoni, Marion; Ruetsch, Caroline; Zorzi, Kévin; Fernandez, Céline; Boyer-Suavet, Sonia; Benzaken, Sylvia; Demonchy, Elisa; Dellamonica, Jean; Ichai, Carole; Esnault, Vincent; Brglez, Vesna; Seitz-Polski, Barbara (Frontiers in Medicine, 2021)
Frontline health care workers (HCWs) have been particularly exposed to Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) since the start of the pandemic but the clinical features and immune responses of those infected with SARS-CoV-2 have not been well described. In a prospective single center cohort study, we enrolled 196 frontline HCWs exposed to the SARS-Cov-2 and 60 patients with moderate and severe forms of the coronavirus disease 2019 (COVID-19). Serological tests and cytokines assay were performed to analyze SARS-CoV-2-specific humoral and cellular immunity. Of the 196 HCWs tested, 15% had specific antibodies against SARS-CoV-2 and 45% of seropositive HCWs were strictly asymptomatic. However, in comparison to moderate and severe forms, HCWs with mild or asymptomatic forms of COVID-19 showed lower specific IgA and IgG peaks, consistent with their mild symptoms, and a robust immune cellular response, illustrated by a high production of type I and II interferons. Further studies are needed to evaluate whether this interferon functional immune assay, routinely applicable, can be useful in predicting the risk of severe forms of COVID-